A triple (e−/O2−/H+) conducting perovskite BaCo0.4Fe0.4Zr0.1Y0.1O3-δ for low temperature solid oxide fuel cell. (26th February 2021) - Jhuang, Jhe-Wei; Lee, Kan-Rong; Lee, Sheng-Wei; Wang, Baoyuan; Xia, Chen; Hung, I.Ming; Tseng, Chung-Jen
Abstract: Low-temperature solid oxide fuel cells (LT-SOFCs) have recently gained enormous attention worldwide with a new research trend focusing on single layer fuel cells (SLFC), which have better cell performance than traditional SOFCs at low operating temperatures. In this study, a triple (e − /O 2− /H + ) conducting perovskite BaCo0.4 Fe0.4 Zr0.1 Y0.1 O3-δ (BCFZY) is used as the intermediate layer material for SLFC. A high current density of 994 mA/cm 2 at 0.6 V and a peak power density of 610 mW/cm 2 with an OCV of 1.01 V has been achieved with a cell operating temperature of 550 °C, confirming the application feasibility of BCFZY in SLFCs. Furthermore, a typical proton conductor BaZr0.8 Y0.2 O3-δ (BZY) is introduced into BCFZY to enhance the cell performance. By adjusting the mass ratio of the BCFZY-BZY layer, an optimal power density is obtained, achieving 703 mW/cm 2 with an OCV of 1.03 V at 550 °C with an 8BCFZY:2BZY (wt%) ratio. These findings prove that the proposed BCFZY-BZY holds great promise for developing SLFCs to realize low-temperature operation. Highlights: A triple conducting BaCo0.4 Fe0.4 Zr0.1 Y0.1 O3-δ is applied in single layer fuel cell. The peak power density of SLFC with pure BCFZY reaches 610 mW/cm 2 at 550 °C. BaZr0.8 Y0.2 O3-δ (BZY) is used to optimize the mixed conductivity. With 20% BZY, the peak power density rises to 703 mW/cm 2 at 550 °C.